2020
DOI: 10.1101/2020.09.01.278481
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid particles facilitate surface-catalyzed cross-seeding by acting as promiscuous nanoparticles

Abstract: Amyloid seeds are nanometre-sized protein particles that accelerate amyloid assembly, as well as propagate and transmit the amyloid protein conformation associated with a wide range of protein misfolding diseases. However, seeded amyloid growth through templated elongation at fibril ends cannot explain the full range of molecular behaviours observed during cross-seeded formation of amyloid by heterologous seeds. Here, we demonstrate that amyloid seeds can accelerate amyloid formation via a surface catalysis me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…This is further supported as the structure of PRL seeded GAL fibril showed similar fibrils morphology and secondary structure as of GAL fibrils formed alone (Fig 3). This is a typical property of surface-mediated secondary nucleation that produce fibrils 56 . Further the PRL seeding to GAL fibril formation was more efficient as compared to homo-seeding of GAL further support surface mediated secondary nucleation 53,56 (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is further supported as the structure of PRL seeded GAL fibril showed similar fibrils morphology and secondary structure as of GAL fibrils formed alone (Fig 3). This is a typical property of surface-mediated secondary nucleation that produce fibrils 56 . Further the PRL seeding to GAL fibril formation was more efficient as compared to homo-seeding of GAL further support surface mediated secondary nucleation 53,56 (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
“…This is a typical property of surface-mediated secondary nucleation that produce fibrils 56 . Further the PRL seeding to GAL fibril formation was more efficient as compared to homo-seeding of GAL further support surface mediated secondary nucleation 53,56 (Fig 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, secondary nucleation might only be a special case of general surface nucleation (Buell, 2017). It has been shown that fibrils of one protein can nucleate from monomer on the surface of fibrils of another protein, while the same proteins are unable to elongate each others fibrils (Koloteva-Levine et al, 2020;Vaneyck et al, 2021). This difference suggests that cross-surface nucleation has much lower requirements for sequence similarity than cross-elongation.…”
Section: Secondary Nucleation and The Preservation Of The Fibril Strainmentioning
confidence: 99%